FAKTOR YANG MEMPENGARUHI LOYALITAS PETERNAK PLASMA DALAM KEMITRAAN USAHA TERNAK AYAM RAS PEDAGING/BROILER RAYON YOGYAKARTA (Kasus di Kemitraan PT. Malindo Feedmill Cabang Yogyakarta) - Maria Pinkan Elionora Sepoetri; Heru Irianto; Nuning Setyowati (Caraka Tani: Journal of Sustainable Agriculture, 2016)
This research aims to know the implementation of the ongoing partnerships in PT Malindo Feedmill branch Yogyakarta, knowing the influence of variable quality of products, service quality, breeder expectation, and corporate image towards the breeders satisfaction, as well as knowing the influence breeders satisfaction towards breeder loyalty. This research uses the basic method of descriptive analytic. This research was carried out at PT. Malindo Feedmill branch Yogyakarta. The method of determining the location of the research done by the purposive method and method of determination of samples is carried out by the census method by the number of samples of 75 respondents. The technique of collecting data through observation, interviews, and questionnaires that have been tested for validity and reliability. The analysis of the data used in this research is a method of Structural Equation Models (SEM) with an alternative method of Partial Least Square (PLS). The results showed that: (1) Partnership patterns in PT Malindo Feedmill. is a core-plasma pattern with a strategy of 'win-win solution', there is a cooperation agreement between the breeders and the company. (2) The product quality does not affect toward breeders satisfaction. (3) The service quality, the breeders expectation and corporate image has a positive influence toward breeders satisfaction. (4) The breeders satisfaction has a positive influence toward breeders loyalty.